Workshop Pembuatan Video Pembelajaran Untuk Pengoptimalan Media E-Learning - Ghulam Asrofi Buntoro; Dwiyono Ariyadi; Indah Puji Astuti (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
The pandemic period requires a change in behavior habits. Not in the learning process in SMK. Interactive learning media will facilitate the delivery of material by the teacher and easily accessible to most students compared to the delivery of text or PowerPoint. To support e-learning content that is already running at SMK Negeri 1 Jenangan, teachers need to be provided with the provision of making learning videos as media to support learning. The training in making video-based learning media is expected to increase teacher competence in independent learning in student learning to learn virtually during the pandemic season. This learning making training video uses the Camtasia application which is easy for all teachers to practice. So the results can add to the content of e-learning that is already used by the school. From the workshops that have been carried out, as many as 20 teachers of SMK Negeri 1 Jenangan Ponorogo who attended the Workshop were able to use Camtasia to make Learning Videos.